A Reflection on Impact and Influence of CGIAR Policy-Oriented Research - Renkow, M. (CGIAR Independent Science and Partnership Council, 2018)
Policy-oriented research (POR)—defined as research aimed at identifying new or improved policies, regulations, or institutions (or their management) that enhance economic, social, and environmental welfare—is an important and growing part of CGIAR portfolio. This paper assesses progress that has been made over the past decade to evaluate the welfare impacts of POR conducted within CGIAR. The paper’s first section reviews recent evaluative efforts and finds that little in the way of quantitative impact assessments has occurred since the publication of a set of quantitative ex post POR impact assessments in 2008. Rather, POR evaluations have taken a more qualitative emphasis, focusing on illuminating impact pathways and establishing the contribution of policy research toward effecting policy outcomes. This review also describes a recently-compiled database of 94 significant policy outcomes attributable to CGIAR policy research.